PERAN GURU DALAM MENINGKATKAN KREATIVITAS SISWA SEKOLAH DASAR MELALUI KEGITAN DAUR ULANG SAMPAH - Baihaqi , Bicky; Hasan , Najib; Ginanjar , Romi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to describe the role of teachers in improving elementary schoolstudents' creativity through waste recycling activities. The research employed a de-scriptive qualitative approach and was conducted at SDN Periuk 6, Tangerang City.The research subjects consisted of the principal, the fourth-grade teacher, andfourth-grade students. Data were collected through observation, interviews, anddocumentation and analyzed using the Miles and Huberman model. The findingsshowed that teachers performed their roles as educators, facilitators, motivators,demonstrators, activity managers, and evaluators in implementing waste recyclingactivities. These roles contributed to improving students' creativity, as reflected intheir ability to utilize recycled materials, develop ideas, collaborate with peers, andproduce creative and useful products. Therefore, waste recycling activities canserve as an alternative learning strategy to enhance elementary school students'creativity.